The Role of Culture of Communication in the Formation of Personality - Nurillaev Khayrullo Olimjon ugli (Zien Journals, 2022)
This article describes the role of the culture of communication in the formation of personality, gives practical advice on the forms and means of communication. The ways of proper communication, the specifics of socio-psychological communication are considered
Keywords: Communication; communication culture; intensification; consciousness